2015
DOI: 10.1038/onc.2015.416
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of MYC with host cell factor-1 is mediated by the evolutionarily conserved Myc box IV motif

Abstract: The MYC family of oncogenes encodes a set of three related transcription factors that are overexpressed in many human tumors and contribute to the cancer-related deaths of more than 70,000 Americans every year. MYC proteins drive tumorigenesis by interacting with co-factors that enable them to regulate the expression of thousands of genes linked to cell growth, proliferation, metabolism, and genome stability. One effective way to identify critical cofactors required for MYC function has been to focus on sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…MYC binds to BRD4 and the pTEFb complex to facilitate transcriptional elongation by release of paused RNA polymerase II [ 60 , 61 ]. The conserved Myc Boxes contribute to transformation with the Myc Box 3b (MB3b) binding to WDR5 and Myc Box 4 (MB4) binding to HFCF1 ( S1 Fig ) [ 62 , 63 ]. MB3a, or simply referred to as MB3, found only in MYC and MYCN and not MYCL, is required for tumorigenic activity of MYC in vitro and in vivo [ 64 ] and contributes to transcriptional repression by recruiting HDAC3 [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…MYC binds to BRD4 and the pTEFb complex to facilitate transcriptional elongation by release of paused RNA polymerase II [ 60 , 61 ]. The conserved Myc Boxes contribute to transformation with the Myc Box 3b (MB3b) binding to WDR5 and Myc Box 4 (MB4) binding to HFCF1 ( S1 Fig ) [ 62 , 63 ]. MB3a, or simply referred to as MB3, found only in MYC and MYCN and not MYCL, is required for tumorigenic activity of MYC in vitro and in vivo [ 64 ] and contributes to transcriptional repression by recruiting HDAC3 [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , Aurora-A competes with binding of TFIIIC and RAD21 to the amino-terminus of N-MYC. A secondary binding site for Aurora-A overlaps with MYCBoxIV, which binds to HCF1, and it is possible, therefore, that Aurora-A also competes with HCF1 for binding to N-MYC ( Thomas et al., 2016 ). In vivo , Aurora-A inhibits chromatin binding of TFIIIC and RAD21 and interactions of N-MYC with RAD21, TOP2A, and TFIIIC in S phase ( Figure 7 G).…”
Section: Discussionmentioning
confidence: 99%
“…Two important phosphorylation sites, Threonine 58 (T58) and Serine 62 (S62), within MBI are critical for the regulation of MYC stability and activity in response to cell growth signals (Farrell and Sears, 2014;. The central region of MYC contains the MBIIIa, MBIIIb, and MBIV which are important for transcriptional activity and proapoptotic activity (Cowling et al, 2006;Kurland and Tansey, 2008;Thomas et al, 2015Thomas et al, , 2016. For example, MBIIIa interacts with the histone deacetylase HDAC3 to suppress transcription and MBIIIb associates with WDR5 to facilitate H3K4 methylation and MYC recruitment to chromatin (Thomas et al, 2015), whereas MBIV association with transcriptional coregulator host cell factor-1 (HCF-1) is critical for MYCdriven tumorigenesis (Thomas et al, 2016; Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…The central region of MYC contains the MBIIIa, MBIIIb, and MBIV which are important for transcriptional activity and proapoptotic activity (Cowling et al, 2006;Kurland and Tansey, 2008;Thomas et al, 2015Thomas et al, , 2016. For example, MBIIIa interacts with the histone deacetylase HDAC3 to suppress transcription and MBIIIb associates with WDR5 to facilitate H3K4 methylation and MYC recruitment to chromatin (Thomas et al, 2015), whereas MBIV association with transcriptional coregulator host cell factor-1 (HCF-1) is critical for MYCdriven tumorigenesis (Thomas et al, 2016; Figure 1A). Recent genome-wide and gene specific studies have revealed several emerging models for MYC function, including specific-gene regulation, global gene activation, and gene-specific affinity models (Kress et al, 2015;Baluapuri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%